ST-Segment elevation acute myocardial infarction prehospital thrombolytic therapy: Chinese expert consensus - Hongbin Yan; Dingcheng Xiang; Hongmei Liu; Hui Chen; Jiyan Chen; Yuguo Chen; Yundai Chen; Yingjie Chu; Weiyi Fang; Xianghua Fu; Chunji Lie; Wei Mao; et al. (Cardiology Plus, 2018)
Acute myocardial infarction (AMI) still seriously threatens the health of the people in our country. The situation is even more severe in the vast urban and rural areas in China. Timely treatment of AMI patients to reduce mortality and protect heart function is very important. Prehospital thrombolysis treatment has great significance in urban and rural areas outside the big cities. To this end, the Chinese Medical Doctor Association's chest pain professional committee and the Chinese Medical Rescue Association's Cardiovascular Emergency Sub-Commission organized relevant experts to formulate this consensus, aiming to help prehospital medical emergency personnel select the best treatment strategies for patients with AMI. However, the final decision on a specific patient should be made by the prehospital emergency personnel together with the patients and their family members.